The Problem of Normative Reflection (Consolidation) of Causation in the Criminal Law of Ukraine and Some Foreign Countries - Владимир, Владимир (PRAWO i WIĘŹ, 2022)
The author raises up an issue of normative reflection (consolidation) of causation in the criminal law of Ukraine and some foreign countries.The author emphasizes that to characterize of causation which is a criminal law category, one must reflect this connection or its prediction in the norms of the Criminal Code of Ukraine and some foreign countries, which belong to the continental legal family. The author provides a comprehensive analysis of the problem of reflecting the causal link in criminal law. He begins by analyzing the concept of legal construction and then he analyzes the terminological problems of causation both in the post-Soviet countries (Georgia, Moldova, Ukraine) and in the EU countries (Spain, France, etc.). The article states that the legal construction of „causation” is reflected in particular in Article 8 of the Criminal Code of Georgia, where the emphasis is put on the fact that causation exists when the act has entailed illegal consequences or created a specific danger of illegal consequences. Within the Criminal Code of Ukraine, a set of commonly used special technical terms is used to reflect the causal link. In this case, the causal link is reflected by these terms within the articles of the Special Part of the Criminal Code of Ukraine and their parts. Within the framework of criminal codified acts of some foreign countries, the reflection of causation is achieved by emphasizing the harmful consequences of the act.